(untitled) (Architecture Image Studies, 2026)
The rapid development of digital technology has reshaped the media ecosystem and transformed patterns of news consumption. Local media organizations are therefore required to adapt through media convergence and visual content innovation. This study examines media convergence, visual news strategies, and audience engagement at Kabar Makassar as a case of local journalism in the era of digital disruption. Using a qualitative case study approach, data were collected through in-depth interviews, observation, and documentation involving editorial, multimedia, and social media teams. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that convergence at Kabar Makassar is realized through cross-divisional collaboration integrating editorial production, multimedia practices, and platform-based distribution. Visual strategies such as short videos, visual slides, and infographics enhance accessibility, interaction, and public responsiveness across TikTok, Instagram, and YouTube Shorts. The study concludes that local media sustainability depends on convergence, visual journalism, and participatory engagement.